Kurzarbeit or short-time work in Slovak Republic? - Švec, Marek; Kubinec, Martin (Technium Social Sciences Journal, 2023)
The new legal framework introduces a novel concept of short-time work involving distinct features from the conventional system. The new Slovakian "kurzarbeit" model is intended to serve as a response to economic fluctuations and sudden interruptions of industrial or work processes. The legal analysis focuses on a comparison of the legal framework in the Short-time Work Support Act and the Slovak Labour Code, with regard to the partial duality of the legal regulation of this labour law institution. The authors aim to clarify the mechanism of functioning and anticipated impacts on the participants of labour relations. The legal analysis focuses on a comparison of the legal framework in the Short-time Work Support Act and the Slovak Labour Code, with regard to the partial duality of the legal regulation of this labour law institution. The aim of the contribution is to point out the significant benefits of the recently established labor law institute, also based on official statistical data of the Ministry of Labour, Social Affairs and the Family of the Slovak Republic.